2008
DOI: 10.1021/jm800841w
|View full text |Cite
|
Sign up to set email alerts
|

Acylguanidines as Bioisosteres of Guanidines: NG-Acylated Imidazolylpropylguanidines, a New Class of Histamine H2 Receptor Agonists

Abstract: N1-Aryl(heteroaryl)alkyl-N2-[3-(1H-imidazol-4-yl)propyl]guanidines are potent histamine H2-receptor (H2R) agonists, but their applicability is compromised by the lack of oral bioavailability and CNS penetration. To improve pharmacokinetics, we introduced carbonyl instead of methylene adjacent to the guanidine moiety, decreasing the basicity of the novel H2R agonists by 4-5 orders of magnitude. Some acylguanidines with one phenyl ring were even more potent than their diaryl analogues. As demonstrated by HPLC-MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(110 citation statements)
references
References 55 publications
3
107
0
Order By: Relevance
“…Histamine Receptors resulting in substantially reduced basicity (by 4-5 orders of magnitude), but retaining H 2 receptor agonistic activity (Ghorai et al, 2008). Unfortunately, as also found for arpromidine-and impromidine-like compounds, numerous N G -acylated imidazolylpropylguanidines (e.g., UR-AK24) proved to be poorly selective for the H 2 receptor.…”
Section: E H 2 Receptor-selective Ligandsmentioning
confidence: 99%
“…Histamine Receptors resulting in substantially reduced basicity (by 4-5 orders of magnitude), but retaining H 2 receptor agonistic activity (Ghorai et al, 2008). Unfortunately, as also found for arpromidine-and impromidine-like compounds, numerous N G -acylated imidazolylpropylguanidines (e.g., UR-AK24) proved to be poorly selective for the H 2 receptor.…”
Section: E H 2 Receptor-selective Ligandsmentioning
confidence: 99%
“…[15] Furthermore, in the field of histamine receptor agonists, acylguanidines were identified as bioisosteres of guanidines or mimics of amino groups. [10,14] Receptor mutagenesis and molecular modeling studies revealed that the guanidino group of the Y 1 R antagonistic (R)-argininamide BIBP3226 and its N G -acylated analogues interact with a highly conserved Asp residue in TM6 of the Y 1 R. [32] In the Y 2 R an Asp residue at the corresponding position is crucial for agonist binding, but does not substantially contribute to binding of BIIE0246. [33,34] Other residues were found to be important for direct antagonist interactions, such as Tyr in TM2 and Leu in TM5.…”
Section: Acylguanidines As Less Basic Bioisosteric Replacements For Gmentioning
confidence: 99%
“…Previously, the replacement of guanidine groups with acyl-or carbamoylguanidine moieties proved to be a very successful bioisosteric approach for histamine H 2 , H 3 , and H 4 receptor ligands, [10][11][12][13][14] and for argininamide-type NPY Y 1 R antagonists [15][16][17] derived from BIBP3226 ( Figure 1). The introduction of various electron-withdrawing substituents at the N G -position of BIBP3226 resulted in analogues with similar or even increased Y 1 R antagonistic activities, [16] and opened a route toward fluorescence-labeled [17,18] and tritiated [15] highly potent Y 1 R antagonists.…”
Section: Introductionmentioning
confidence: 99%
“…Since the hH 4 R-GAIP fusion protein, compared to the standard co-expression system (hH 4 R + G i2 + G 1  2 ), resulted in an increased signal-to-noise ratio with unchanged ligand potencies and efficacies, we decided to use hH 4 R-GAIP (+ G i2 + G 1  2 ) as a standard test system for the characterization of hH 4 R ligands in our medicinal chemistry program [39,40]. M a n u s c r i p t 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 20 - Fig.…”
Section: Characterization Of Standard Ligands At Hh 4 R Hh 4 R-rgs4 mentioning
confidence: 99%